Penerapan Teknologi Pemasaran Digital Bagi Masyarakat UMKM Dusun Brajan di Gedung Tani Banjararum - Murdiyanto, Aris Wahyu; Rahayu, Suparni Setyowati; Sutanta, Edhy; Hanafi, Ahmad; Rosid, Ibnu Abdul; Arbintarso, Ellyawan Setyo; -, Purnawan (Journal of Dedicators Community, 2024)
Community service activities carried out in Banjararum Village, Kapanewon Kalibawang, Kulon Progo Regency, DIY, on November 4 2023 aim to provide solutions to the problems faced by three Non-Governmental Organizations (NGOs), namely the Punthuk Ngepoh Tourism Awareness Group (Pokdarwis). , Srikandi Farming Women's Group (KWT), and Gapoktan Ngudi Makmur. The problems faced include the absence of an optimal electricity network, the absence of infographic information/spatial plans for the Punthuk Ngepoh Tourist Attraction, the absence of a digital marketing platform, the absence of cassava cutting tools, lack of water in agricultural areas during the dry season, manure from livestock which causes disturbances in the form of unpleasant odors and there is no management of livestock manure. The solutions include repair and development of solar panels as well as the process of exploring springs in Punthuk Ngepoh to be used as a tourism support facility, the application of TTG in the form of a cassava cutting tool, and the application of TTG in the form of gasification in the coconut oil extraction process. Community service activities in the Banjararum District have provided solutions to the problems faced by the three NGOs. It is hoped that the solutions offered can boost the community's economy through programs created by the NGO.